Evidence for high-energy and low-emittance electron beams using ionization injection of charge in a plasma wakefield accelerator. (9th February 2016) - Vafaei-Najafabadi, N; An, W; Clayton, C E; Joshi, C; Marsh, K A; Mori, W B; Welch, E C; Lu, W; Adli, E; Allen, J; Clarke, C I; Corde, S; et al.
Abstract: Ionization injection in a plasma wakefield accelerator was investigated experimentally using two lithium plasma sources of different lengths. The ionization of the helium gas, used to confine the lithium, injects electrons in the wake. After acceleration, these injected electrons are observed as a distinct group from the drive beam on the energy spectrometer. They typically have a charge of tens of pC, an energy spread of a few GeV, and a maximum energy of up to 30 GeV. The emittance of this group of electrons can be many times smaller than the initial emittance of the drive beam. The energy scaling for the trapped charge from one plasma length to the other is consistent with the blowout theory of the plasma wakefield.